Ascitic fluid analysis with special reference to serum ascites cholesterol gradient and serum ascites albumin gradient - Sastry, Anand Sankar; Mahapatra, Subash Ch.; Dumpula, Vidyasagar (International Journal of Research in Medical Sciences, 2017)
Background: Ascites being a common clinical problem with a vast spectrum of etiologies, less expensive and widely available biochemical parameters are required to differentiate ascites which can correlate with pathogenesis and pin point towards an etiology with high sensitivity and significant accuracy. Aims of the study were to determine the sensitivity, specificity and diagnostic efficacy of serum ascites albumin Gradient (SAAG) and that of ascitic fluid total protein (AFTP), evaluating their diagnostic role in identifying the etiology of ascites, to determine the diagnostic efficacy of Ascitic fluid cholesterol and serum ascites cholesterol gradient (SACG) in diagnosis of malignant ascites. Methods: In this study, 100 patients of ascitis were evaluated for ascitic fluid total protein, albumin, cholesterol, SAAG and SACG along with ultrasound and other required investigations. Results: Sensitivity, Specificity, and Diagnostic accuracy of SAAG for Portal hypertension were 97%, 85%, 96% respectively, whereas those of AFTP for exudative/transudative ascitis were 78.5%, 66%, 68% respectively. Ascitic fluid cholesterol and Mean SACG were significantly elevated in malignant ascites when compared with Non-Malignant Ascitis with p=0.0001. Similarly with a cut off level of 70mg% and 54 mg%, Ascitic fluid cholesterol and Mean SACG are having diagnostic accuracy of 90% and 93% respectively. Conclusions: SAAG is much more superior to AFTP in differential diagnosis of Ascitis. Ascitic fluid cholesterol and Mean SACG are simple and cost effective methods to separate malignant ascitis from non-malignant causes even in small centres with limited diagnostic facilities.